2022
DOI: 10.1371/journal.pone.0273971
|View full text |Cite|
|
Sign up to set email alerts
|

Sure-thing vs. probabilistic charitable giving: Experimental evidence on the role of individual differences in risky and ambiguous charitable decision-making

Abstract: Charities differ, among other things, alongside the likelihood that their interventions succeed and produce the desired outcomes and alongside the extent that such likelihood can even be articulated numerically. In this paper, we investigate what best explains charitable giving behaviour regarding charities that have interventions that will succeed with a quantifiable and high probability (sure-thing charities) and charities that have interventions that only have a small and hard to quantify probability of bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…These values help people see their connection to others and the impact they can have on the world. The findings of this study are particularly useful for non-profit organizations that seek to attract and retain individual charitable donors and may also help to increase revenue frequency, obtain higher amounts of resources, and solicit donations to both religious and secular organizations (Schoenegger & Costa-Gomes, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…These values help people see their connection to others and the impact they can have on the world. The findings of this study are particularly useful for non-profit organizations that seek to attract and retain individual charitable donors and may also help to increase revenue frequency, obtain higher amounts of resources, and solicit donations to both religious and secular organizations (Schoenegger & Costa-Gomes, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…While research has found that reliance on hypothetical donations increases mean donations (Bekkers, 2017), to our knowledge, there is no evidence that hypotheticality influences differences between conditions in WTD judgments. Finally, incentive compatible studies typically provide an endowment and ask participants to donate a proportion of this (e.g., Schoenegger & Costa‐Gomes, 2022; Small et al, 2007), which is a considerably different task from the majority of real‐life donation decisions. Given that our participants appeared to take the WTD task seriously (as evidenced above), we would see such an incentive compatible task as more different from real donation decisions than our hypothetical tasks, especially as it induces an upper bound on how much participants can donate (the endowment), which would make it more difficult to study scope sensitivity.…”
Section: Discussionmentioning
confidence: 99%